Practice-based innovation: insights, applications and policy implications : understanding practice-based innovation and its policy implications - Harmaakorpi, Vesa; Melkas, Helinä (Springer Berlin Heidelberg, 2012)
The book describes and analyses the new environment for innovation, it does this with an emphasis on yet uncharted regions within the field of practice-based innovation, coming up with guidelines for innovation policy measures needed in order to realise this. While it focuses on these policies it also takes into account multi-actor innovation processes, user-driven innovation, "related variety" and many other aspects; aspects such as, just to name a few: communicating creative processes and distributing practice-based innovation; then there is creativity itself, encompassing new fields of knowledge and expertise. The authors go on to describe value networks, showing how to make practice-based innovations, explaining innovation diffusion and absorptive capacity. The book presents new insights as well as the latest research related to the frequently used term "innovation". Definitions are put forward, giving, by way of examples, a detailed description of concepts we draw upon when using these. Innovation as a concept is constantly being subdivided into increasingly finer distinctions, which, in turn, determine the discourse. The book takes a close look at these, further taking into account the challenges as well as the opportunities inherent in developing practice-based innovation procedures and policies of global importance, never losing sight of advancing long-term   effectiveness.